2022
DOI: 10.1212/wnl.0000000000200945
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Eicosanoid Levels With Immune, Viral, and Cognitive Outcomes in People With HIV

Abstract: Objective.To determine if plasma eicosanoid levels are associated with immune, viral, and cognitive outcomes in people with the human immunodeficiency virus (PWH).Methods.We measured 42 eicosanoids in a longitudinal study of 95 PWH and 25 demographically comparable uninfected participants. Routine clinical chemistry, virologic, immune markers and a neuropsychological test battery assessing seven cognitive domains was administered to all participants at two study visits over an average of 6.5 months.Results.Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Coherently with an in-vivo deregulation of eicosanoids' metabolism, previous reports suggested that arachidonic acid levels may be increased in the CSF of HIV-1 patients with neurocognitive impairment [21]. Additionally, more recent studies confirmed that plasma eicosanoids are increased in PWH, correlate directly with viral load and negatively with cognitive performances, and are persistently elevated also in ART-treated persons with neurological impairment [24,42].…”
Section: Discussionmentioning
confidence: 97%
“…Coherently with an in-vivo deregulation of eicosanoids' metabolism, previous reports suggested that arachidonic acid levels may be increased in the CSF of HIV-1 patients with neurocognitive impairment [21]. Additionally, more recent studies confirmed that plasma eicosanoids are increased in PWH, correlate directly with viral load and negatively with cognitive performances, and are persistently elevated also in ART-treated persons with neurological impairment [24,42].…”
Section: Discussionmentioning
confidence: 97%
“…There are limited studies associating eicosanoids with HIV infection and particularly with HAND. 8 Deme et al 3 show an increase in proinflammatory eicosanoid plasma levels in HIV-infected participants, which was independent from viral load or ART treatment at baseline evaluation (visit 1). However, the eicosanoid plasma levels in HIV-infected participants were associated with lower current and nadir CD4 lymphocyte counts.…”
mentioning
confidence: 93%
“…In the brain, HIV infection promotes and perpetuates chronic neuroinflammation with an eventual irreversible brain injury and HIV-associated neurocognitive disorder (HAND). 1,2 In this issue of Neurology, Deme et al 3 published a study evaluating the association between eicosanoids and cognition in an observational cross-sectional and longitudinal cohort of PWH and the way that antiretroviral treatment (ART) modifies this association. The study used clinical data and plasma samples from 95 PWH and 25 matched controls enrolled in the CNS HIV Anti-Retroviral Therapy Effects Research.…”
mentioning
confidence: 99%